2004
DOI: 10.1242/jcs.01339
|View full text |Cite
|
Sign up to set email alerts
|

β-actin is required for mitochondria clustering and ROS generation in TNF-induced, caspase-independent cell death

Abstract: Comparable NF-κB activation and p38 phosphorylation in TNF-treated wild-type and Actin mut cells also indicates that reduced expression of actin only selectively blocked some of the TNF-induced cellular changes. Actin cleavage involved in apoptosis does not occur in TNF-treated L929 cell death, as in HeLa cells. Consistent over-expression of a caspase-cleaved product, a 15 kDa actin fragment, had no effect on TNF-induced necrosis of L929 cell. By contrast, TNF-induced mitochondria clustering and ROS production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 55 publications
(92 reference statements)
0
47
0
1
Order By: Relevance
“…The aggregation of mitochondria in the perinuclear region of postmitotic cells can have different reasons. Perinuclear clustering of mitochondria has been observed in apoptosis as well as in necrosis (Thomas et al, 2000;Li et al, 2004) but we did not observe any caspase-3 activation in adherent postmitotic cells (data not shown), indicating that cells were not undergoing apoptosis. Overexpression of fusion proteins Mfn1 and Mfn2 in Hela cells also resulted in clustering of interconnected mitochondria (Eura et al, 2003).…”
Section: Discussionmentioning
confidence: 57%
“…The aggregation of mitochondria in the perinuclear region of postmitotic cells can have different reasons. Perinuclear clustering of mitochondria has been observed in apoptosis as well as in necrosis (Thomas et al, 2000;Li et al, 2004) but we did not observe any caspase-3 activation in adherent postmitotic cells (data not shown), indicating that cells were not undergoing apoptosis. Overexpression of fusion proteins Mfn1 and Mfn2 in Hela cells also resulted in clustering of interconnected mitochondria (Eura et al, 2003).…”
Section: Discussionmentioning
confidence: 57%
“…However, previous studies suggest the existence of mitochondria or/ and caspases-independent cell death in programmed cell death (PCD). For instance, it has been variously reported that apoptotic pathway was activated by stimuli in a mitochondria-dependent and -independent (MacDonald et al, 1999) or caspase-independent (Kang et al, 2004;Li et al, 2004;Shrivastava et al, 2006;Zhang et al, 2011) or both mitochondria-and caspase-independent manner (Chauhan et al, 2004;Bhalla et al, 2009). Our results showed that Dic did not induced any mitochondrial depolarization and caspase-3 inhibition did not prevent Dic-induced A549 cell death indicating that Dic induced a mitochondria-and caspase-3-independent A549 cell apoptosis (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In our attempts to determine such a molecule, we blocked IFN-␥, IFN␣, FasL, and TRAIL; however, the neutralization of these molecules alone or in combination did not rescue NB cells from the AS-induced "delayed" death (data not shown). TNF-␣ can trigger caspase-dependent and caspase-independent cell death; the latter can be mediated by cathepsin B or reactive oxygen species in tumors of different origin (24,26,36,37). Currently available cathepsin B inhibitors, including CA074Me, did not prevent the "delayed" death in NBs.…”
Section: Discussionmentioning
confidence: 99%